Diastemas: reestablishment of an attractive smile - Castro, Mara Antonio Monteiro de [UNESP]; Castro, José Carlos Monteiro de [UNESP]; Pedrini, Denise [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP] (My University, 2010)
A healthy and attractive smile is very valued in today s society. Yet this requires better aesthetic and cosmetic solutions from dental surgeons.The present paper presents a case report of diastema closure using an association of tooth movement induced by orthodontic elastics,dental cosmetics and resin-bonded prosthesis. The female patient L.B.A.J., aged 19 years, visited the Integrated Clinic of Araçatuba DentalSchool UNESP mainly complaining of missing teeth and poor esthetics. After anamnesis, clinical and radiographic examination revealedhypodontia of the maxillary right and left first premolars, abnormal maxillary right lateral incisor shape and diastema between the maxillaryright lateral incisor and canine and between the maxillary left lateral incisor and canine. Planning was done which included indication ofdiastema closure with composite resin restoration and metal-free resin-bonded prosthesis, with a structure made of Vectris (Ivoclar VivadentInc., Amherst, NT, USA). The option for dental cosmetics associated with resin-bonded prosthesis after movement with orthodontic elasticsresulted in an excellent aesthetic outcome of low cost and short treatment duration.Indexing terms: composite resins; diastema; fixed resin bonded partial denture.

Ter um sorriso saudável e harmônico representa grande valor na sociedade atual. Para esta condição, exigem-se melhores soluções estéticas e cosméticas pelos cirurgiões-dentistas. O objetivo deste artigo é apresentar um caso clínico de fechamento de diastema utilizando a associação da movimentação dentária por meio de borrachas ortodônticas, com a plástica dentária e a prótese fixa adesiva. Paciente L.B.A.J., sexo feminino, 19 anos, procurou o serviço da Clínica Integrada da Faculdade de Odontologia de Araçatuba da Universidade Estadual Paulista Júlio de Mesquita com queixa de ausência de dentes e estética comprometida. Após anamnese, exame clínico e radiográfico foi diagnosticado agenesia dos dentes 14 e 24, alteração de forma do 12 e diastema entre o 12 e 13 e o 22 e 23. Foi realizado o planejamento, com indicação de fechamento de diastema, com restauração de resina composta e prótese fixa adesiva sem metal, com estrutura em Vectris (Ivoclar Vivadent Inc., Amherst, NT, USA). A opção pela plástica dentária associada à prótese fixa adesiva, após movimentação com borrachas, mostrou-se um excelente resultado estético com menor custo e tempo de tratamento.
Diastemas: restabelecimento da harmonia do sorriso
Keywords: Composite resins; Diastema; Fixed resin bonded partial denture; Resinas compostas; Diastema; Prótese adesiva